Safety and Efficacy of the NVX-CoV2373 Coronavirus Disease 2019 Vaccine at Completion of the Placebo-Controlled Phase of a Randomized Controlled Trial. (10th October 2022) - Heath, Paul T; Galiza, Eva P; Baxter, David Neil; Boffito, Marta; Browne, Duncan; Burns, Fiona; Chadwick, David R; Clark, Rebecca; Cosgrove, Catherine A; Galloway, James; Goodman, Anna L; Heer, Amardeep; et al.
Abstract: Background: The recombinant protein-based vaccine, NVX-CoV2373, demonstrated 89.7% efficacy against coronavirus disease 2019 (COVID-19) in a phase 3, randomized, observer-blinded, placebo-controlled trial in the United Kingdom. The protocol was amended to include a blinded crossover. Data to the end of the placebo-controlled phase are reported. Methods: Adults aged 18–84 years received 2 doses of NVX-CoV2373 or placebo (1:1) and were monitored for virologically confirmed mild, moderate, or severe COVID-19 (onset from 7 days after second vaccination). Participants who developed immunoglobulin G (IgG) against nucleocapsid protein but did not show symptomatic COVID-19 were considered asymptomatic. Secondary outcomes included anti-spike (S) IgG responses, wild-type virus neutralization, and T-cell responses. Results: Of 15 185 participants, 13 989 remained in the per-protocol efficacy population (6989 NVX-CoV2373, 7000 placebo). At a maximum of 7.5 months (median, 4.5) postvaccination, there were 24 cases of COVID-19 among NVX-CoV2373 recipients and 134 cases among placebo recipients, a vaccine efficacy of 82.7% (95% confidence interval [CI], 73.3%–88.8%). Vaccine efficacy was 100% (95% CI, 17.9%–100.0%) against severe disease and 76.3% (95% CI, 57.4%–86.8%) against asymptomatic disease. High anti-S and neutralization responses to vaccination were evident, together with S-protein–specific induction of interferon-γ secretion in peripheral blood T cells. Incidence of serious adverse events and adverse events of special interest were similar between groups. Conclusions: A 2-dose regimen of NVX-CoV2373 conferred a high level of ongoing protection against asymptomatic, symptomatic, and severe COVID-19 through >6 months postvaccination. A gradual decrease of protection suggests that a booster may be indicated. Clinical Trials Registration: EudraCT, 2020-004123-16. Abstract : In a phase 3 trial, a 2-dose regimen of the NVX-CoV2373 coronavirus disease 2019 (COVID-19) vaccine conferred a high level of protection against asymptomatic, symptomatic, and severe COVID-19 through >6 months postvaccination.